Neurosurgery Research Productivity in Latin American and Caribbean Countries: A Bibliometric and Visualized Study - Visconti-Lopez, Fabriccio J. (2022)
Objectives: Determine the bibliometric characteristics of scientific articles that address the subject of neurosurgery in Latin America and the Caribbean. Methods: A bibliographic search of original articles published in the Web of Science database up to 2021 was performed, without language restrictions. The terms included in the search strategy were Neurosurgery, neurosurgical procedures, and neurological surgical procedure. Articles according to the inclusion criteria in the Rayyan application were included. Subsequently, a quantitative bibliometric analysis was carried out with the bibliometrix package in R and VOSviewer. Results: We identified 882 articles published in 271 journals. The first publication was in 2006, the highest number of publications was in 2021, the annual percentage growth rate was 25.9, and the average number of citations per document was 11.2. The author with the highest number of publications was Teixeira MJ (41 articles), and the University of Sao Paulo had the highest number of articles on this topic. WORLD NEUROSURGERY was the journal with the most publications (120 articles), and the study by Carney et al (2017) was the most cited (1175 citations). The country of corresponding authors with the most publications and the greatest number of total citations was Brazil. Surgery, and Management were the most used keywords plus; however, in the most recent articles Simulation and Guidelines were used. Conclusions: In the past decade, there has been an increase in articles on neurosurgery in Latin America and the Caribbean. Scientific production in neurosurgery must continue to increase in order to promote evidence-based medicine.